Lead Time Breach of Document Handover Affecting Procurement Process and Occurring Detention - Alam, Mohammed Ifekharul (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.